Anteseden Kebijakan Dividen pada Perusahaan Konstruksi Periode 2015-2019 - Muhammad Noviar Rahman; Atma Hayat (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2025)
This research is aimed to analyze dividend policy’s antecedent variables which consists of capital structure, liquidity, company growth and profitability of construction companies listed in Indonesia Stock Exchange (BEI) in the 2015-2019 period. This research used secondary data which obtained using documentation techniques, namely taking the data from company’s annual reports published by Indonesia Stock Exchange in the 2015-2019 period. This research used Purposive Sampling as the sampling technique. The data obtained are 40 data from 8 construction company that became the sample. Multiple Linier Regression is used as the analysis technique and the hypothesis is tested using T Test with a significant level of 5%. The result shows that profitability has a significant effect on dividend policy of construction companies, while capital structure, liquidity and company growth do not have a significant effect on dividend policy of construction companies.